Concepts and Theories of Punishment in Islamic Criminal Law - Salwa Refanny; Muhammad Syahzan Haraharap (Jurnal Sahabat ISNU SU, 2024)
From a legal perspective, criminal punishment is part of the law enforcement apparatus that has a normative basis and ethical objectives rooted in the values of Islamic Sharia. This study focuses on an in-depth examination of the concept of criminal punishment, the theories underpinning it, and the forms of punishment in Islamic criminal law, along with their relevance to the development of the modern legal system today. This study employs a qualitative method with a juridical-normative approach through a literature review drawn from Islamic legal texts and various relevant and credible scholarly references. The research findings indicate that the structure of punishment in Islamic criminal law is divided into three main categories: hudud, qisas-diyat, and ta’zir, each of which reflects the principles of legal certainty, justice, and proportional flexibility. Furthermore, the theory of punishment in Islam encompasses retributive, preventive, and corrective approaches that function in an integrated and complementary manner to achieve the overall objectives of the law. Thus, punishment in Islamic criminal law is not merely repressive but also serves preventive and educational functions in fostering social order and the sustainable well-being of society.